Reforming the United Nations: New Initiatives and Past Efforts : Volume 1 - Müller, Joachim (Reforming the United Nations., 1997)
This three-volume set describes and brings together 50 key reform proposals originating inside and outside the United Nations. The documentation contained in this publication touches upon all aspects of the United Nations and covers the full spectrum of proposals and initiatives. It is hoped that the information provided will assist those involved in current efforts in reassessing and reshaping the Organization and will serve as a useful reference set for policy makers, researchers and the interested public.